Hyperelliptic Curves for the Vector Decomposition Problem over Fields of Even Characteristic - Seungkook Park (Journal of Applied Mathematics)
We present an infinite family of hyperelliptic curves of genus two over a finite field of even characteristic which are suitable for the vector decomposition problem.